1993
DOI: 10.1152/jappl.1993.75.4.1615
|View full text |Cite
|
Sign up to set email alerts
|

Neutral endopeptidase inhibition attenuates development of hypoxic pulmonary hypertension in rats

Abstract: Neutral endopeptidase (NEP) inhibition is thought to blunt hypoxic pulmonary hypertension by reducing atrial natriuretic peptide (ANP) metabolism, but this hypothesis has not been confirmed. We measured NEP activity, guanosine 3',5'-cyclic monophosphate (cGMP) production, plasma ANP levels, and cardiac ANP synthesis in rats given an orally active NEP inhibitor (SCH-34826) during 3 wk of hypoxia. Under normoxic conditions, SCH-34826 had no effect on plasma ANP levels but reduced pulmonary and renal NEP activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
1
14
0
2
Order By: Relevance
“…ANP activity is associated with an increase in guanosine 3':5'-cyclic monophosphate (cyclic GMP) (Tremblay et al, 1985). In the study by Klinger et al (1993b), SCH 42495 reduced pulmonary and renal NEP activity by 50% but as in our study, plasma ANP was significantly decreased. The significant increase in urinary levels of cyclic GMP seen by Klinger et al suggests that the biological activity of ANP is increased by NEP inhibition.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…ANP activity is associated with an increase in guanosine 3':5'-cyclic monophosphate (cyclic GMP) (Tremblay et al, 1985). In the study by Klinger et al (1993b), SCH 42495 reduced pulmonary and renal NEP activity by 50% but as in our study, plasma ANP was significantly decreased. The significant increase in urinary levels of cyclic GMP seen by Klinger et al suggests that the biological activity of ANP is increased by NEP inhibition.…”
Section: Discussionsupporting
confidence: 44%
“…Similarly, Klinger et al (1993b) showed that rats treated with the less potent NEP inhibitor, SCH 34826 (90 mg kg-'; twice daily) during 3 weeks of chronic hypoxia had a significantly lower degree of right ventricular hypertrophy, and less pulmonary vascular remodelling, despite a significant reduction in plasma ANP levels. How then does NEP inhibition lead to modification of the cardio-pulmonary response to hypoxia without elevation of plasma ANP?…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Neutral endopeptidase is a major enzymatic pathway for the degradation of BNP and also plays a role in kinin and adrenomedulin breakdown. 193 Inhibition of NEP increases plasma levels of BNP 193 and has been shown to inhibit hypoxic pulmonary hypertension in rats, 194 although the mechanism by which this was achieved is not known.…”
Section: Dovepressmentioning
confidence: 99%
“…Early studies, conducted with inhibitors of NEP, suggested that this peptidase may contribute to chronic hypoxic PHTN. 24,25 However, recent observations in other systems support the possibility that NEP could actually be protective against PHTN, through both peptidase-dependent (eg, degradation of selected vasoactive neuropeptides) and peptidase-independent (eg, complex formation of NEP's intracellular cytosolic domain with signaling molecules) mechanisms. 26 Even the peptidase-dependent effects may extend beyond neuropeptide targets.…”
mentioning
confidence: 99%